Optimizing Learning Outcomes in Islamic Education Subjects Through the Implementation of the Make a Match Learning Model - Susandi Susandi; Zailani Zailani (Al-Fikru)
This study analyzes the effect of the application of the make a match learning model on the learning outcomes of Islamic religious education subjects of seventh grade students of SMP Negeri 4 Tanjung Beringin. The approach used in this research is class action. By using a cycle of planning, action, observation, and follow-up. Data collection techniques were carried out by means of observation, documentation, and tests. The population of this study amounted to 200 people, namely all students of SMP Negeri 4 Tanjung Beringin. The sample in this study used purposive sampling technique, the number was 28 students. Data analysis consists of prerequisite tests, namely normality test, and homogeneity, then hypothesis testing using t-test. The results showed that the application of the Make a match strategy to improve student learning outcomes at SMP Negeri 4 Tanjung Beringin showed that in cycle I who obtained a complete score of the minimum completeness criteria was 78.6% with an average student learning outcome score of 75. In Cycle II students who obtained a complete score of the minimum completeness criteria were 100% and student learning outcomes increased to an average of 82.5. Thus there is an influence of the application of the make a match learning strategy in improving student learning outcomes.